Breaking the Ice: Identifying Hydraulically Forced Crevassing. Issue 21 (30th October 2020) - Hudson, T. S.; Brisbourne, A. M.; White, R. S.; Kendall, J. M.; Arthern, R.; Smith, A. M.
Abstract: Hydraulically forced crevassing is thought to reduce the stability of ice shelves and ice sheets, affecting structural integrity and providing pathways for surface meltwater to the bed. It can cause ice shelves to collapse and ice sheets to accelerate into the ocean. However, direct observations of the hydraulically forced crevassing process remain elusive. Here we report a novel method and observations that use icequakes to directly observe crevassing and determine the role of hydrofracture. Crevasse icequake depths from seismic observations are compared to a theoretically derived maximum dry crevasse depth. We observe icequakes below this depth, suggesting hydrofracture. Furthermore, icequake source mechanisms provide insight into the fracture process, with predominantly opening cracks observed, which have opening volumes of hundredths of a cubic meter. Our method and findings provide a framework for studying a critical process that is key for the stability of ice shelves and ice sheets and, therefore, future sea level rise projections. Key Points: We demonstrate a novel method for using crevasse icequake depths to discriminate between dry and hydrofracture driven surface crevassing Icequakes can be used to directly observe and elucidate the crevasse hydrofracture process Icequakes show tensile crack failure with opening volumes calculated from moment magnitudes